Teaching Reading Differently: Exploring Indonesian PPG Graduates’ Strategies and Barriers in Differentiated Assessment Implementation - Moh. Isnaini (Paramasastra : Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2025)
Abstract This research is aimed to explore the practice of Differentiated Reading Assessment (DRA) in the classroom implementation conducted by PPG (Pendidikan Profesi Guru) (Pre-Service Teacher-Professional Education) graduates in Indonesian junior high schools along with their applied classroom strategies and encountered problems. A qualitative case study was employed in data collection from class observations, lesson plan examination and semi-structured interviews. Results indicate four large strategies teachers used to develop these practices: flexible grouping, choice of text and response modality, tactics for multimodal and culturally responsive assessments, and formative feedback. However, such pedagogical strategies were hampered by systemic and institutional barriers such as time pressure, resource shortage, deficit of assessment literacy and policy drivers focused on standardized testing. The study calls for systemic reform which includes improved teacher training, greater curricular flexibility, funding for instructional materials, and supportive administrative leadership. These changes are necessary to ensure sustainable DRA application and to create more equal and inclusive classrooms across Indonesian schools. Keywords: Differentiated assessment, reading instruction, PPG graduates, assessment literacy.